Pengembangan Kurikulum KKNI Berbasis Entrepreneurship Pada Prodi Manajemen Pendidikan Islam - Subandi Subandi; Dedi Lazwardi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The formulation of curriculum was able to provide directions and references as well as being an effective road map to achieving competence in the implementation of learning. The success of entrepreneurial growth in Indonesia in 2016 ranged from 3.1% and Small Business Regulated 7.1% of 252 million population. Hence, the curriculum of Islamic Higher Education should develop to provide solutions for entrepreneurship. The purpose of this study was to describe the development of the National Qualification Framework on Islamic Education Management (KKNI MPI) curriculum based on entrepreneurship, and substantially describe the profile of graduates, the determination of competency achievement, description and the steps of the lecture and the structure of the course. In collecting data the researchers used descriptive method through the inductive approach, derived from interviews, observation and documentation. The result showed that Islamic Education Management graduate profile formulation was to be the manager of education and training bodies and have an entrepreneurial spirit, 2). Learning outcome (lo) was 38 items consisting of attitude competencies, specialized knowledge and skills, 3). Formulation of lecture that are integrated with entrepreneurship were divided into 49 courses spread out a number of 157 credits which must be taken 148 credits with 9 credits of elective courses. The implication of this research was has, the spirit of developing a curriculum together (collaborative) between lecturers, business world and curriculum users, the emergence of shared awareness to design and evaluatethe curriculum on a regular basis. Key words : Development KKNI Curriculum, Entrepreneurship, Islamic Education Management